MIMICRY OF OBJECTS WITH TRANSFORMATION OPTICS APPROACH - Vyunnik, V. I.; Zvyagintsev, A. A. (Видавничий дім «Академперіодика», 2013)
The possibility is shown to creation of anisotropic dielectric cloakswhich provide the bodies they cover with a mimicry imitating thebody of some other form which can be thus observed by theoutside observer. The technique of designing mimicry cloaks withthe use of transformation optics approach is presented. It is shownthat the material parameters in such a mimicry cloak are of anonsingular character. Numerical modelling of mimicry cloaksis carried out, and their work efficiency estimated.